Fabrication of multi-scale periodic surface structures on Ti-6Al-4V by direct laser writing and direct laser interference patterning for modified wettability applications. (November 2017) - Huerta-Murillo, D.; Aguilar-Morales, A.I.; Alamri, S.; Cardoso, J.T.; Jagdheesh, R.; Lasagni, A.F.; Ocaña, J.L.
Highlights: Square µ-structures were made by Direct Laser Writing with nanosecond laser pulses. Dot-like micro-pillars were fabricated by Direct Laser Interference Patterning. LIPSS were also produced with DLIP creating dual-scale periodic surface structures. Hierarchical structures on Ti-6Al-4V were made combining two laser techniques. Hierarchical structures were hydrophobic and recorded a SCA value over 110°. Abstract: In this work, hierarchical surface patterns fabricated on Ti-6Al-4V alloy combining two laser micro-machining techniques are presented. The used technologies are based on nanosecond Direct Laser Writing and picosecond Direct Laser Interference Patterning. Squared shape micro-cells with different hatch distances were produced by Direct Laser Writing with depths values in the micro-scale, forming a well-defined closed packet. Subsequently, cross-like periodic patterns were fabricated by means of Direct Laser Interference Patterning using a two-beam configuration, generating a dual-scale periodic surface structure in both micro- and nano-scale due to the formation of Laser-Induced Periodic Surface Structure after the picosecond process. As a result a triple hierarchical periodic surface structure was generated. The surface morphology of the irradiated area was characterized with scanning electron microscopy and confocal microscopy. Additionally, static contact angle measurements were made to analyze the wettability behavior of the structures, showing a hydrophobic behavior for the hierarchical structures.